Communicating Luxury Through the Concept of Unconventional Luxury via Imagery Advertising - Potavanich, Tisiruk; Arukaroon, Benjawan (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2024)
This study investigates the effectiveness of imagery advertising in communicating unconventional luxury concepts and how this impacts consumer perceptions of mass-market products. The research explores how visual narratives incorporating elements of transformation, sustainability, and aspirational themes (fantasy dreams, escapism, and high cultural capital) influence young adults’ luxury perceptions in Thailand. Employing a quantitative approach, the study analyzed responses from 400 participants aged 18-30 to AI-generated imagery ads across automotive, electronics, and consumer goods sectors. The results indicate that imagery advertising effectively communicated unconventional luxury concepts, with participants demonstrating clear comprehension of intended narratives. Analysis using Spearman’s rank correlation coefficient revealed positive relationships between these elements and perceived luxury levels. These findings suggest that while imagery advertising can successfully convey unconventional luxury concepts, their impact on elevating mass-market products’ luxury perceptions varies in strength. The study contributes to marketing communication practice by providing empirical evidence for effective visual storytelling strategies in luxury brand development, particularly in emerging markets targeting young consumers, while highlighting innovative approaches to bridge the gap between mass-market offerings and luxury perceptions.